THE IMPLEMENTATION OF CONTEXTUAL, CONSOLIDATING, RECEIVING, RECOGNIZING, RETAINING, RETIEVING, AND RECYCLING (2C-5R) MODEL TO ENCHANCE THE STUDENTS ENGLISH VOCABULARY AT SMP GOWA RAYA MAKASSAR - Rosmaladewi; Akib, Erwin; Junaid (FKIP Unismuh Makassar, 2023)
This research applied a pre-experimental method that spending two months periot of time to ceollectdata using pre-tes, treatment, and post-test. Data were taken from 21 srudents using a total sampling technique from the second grade of Gowa Raya Junior High School. the researcher found that the studets' vocabulary wa very slow, but after the treatment their vocabulary knowledge increased significantly as evidenced by the students' average results.The results of this study indicate that the difference in students' words is a significant difference between the pre-test and post-test score. And the mean score of pre-test was 67.52, and the mean scoree of post-test was 84.47. It can be seen the improvment of pre-test and post-test was 16.96% then calculate the t-test value for vocabulary is 11.18 t-table is 2.086. the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It can be conclude that that the use of the 2C5R model can improve student achievement, especially for Gowa Raya high school students.